The new Cambridge history of the bible / 4 From 1750 to the present / ed. by John Riches - Riches, John Kenneth (The new Cambridge history of the bible, 2015)
This volume examines the Bible's role in the modern world - beginning with a treatment of its production and distribution that discusses publishers, printers, text critics, and translators and continuing with a presentation of new methods of studying the text that have emerged, including historical, literary, social-scientific, feminist, postcolonial, liberal, and fundamentalist readings. There is a full discussion of the changes in understandings of and approaches to the Bible in various faith communities. The dissemination of the Bible throughout the globe has also produced a host of new interpretations, and this volume provides a comprehensive geographical survey of its reception. In the final chapters, the authors offer a thematic overview of the Bible in relation to literature, art, film, science, and other disciplines. They demonstrate that, in spite of challenges to the Bible's authority in western Europe, it remains highly relevant and influential, not least in the Americas, Africa, and Asia